The feasibility of discriminating BRONJ lesion bone with Raman spectroscopy - Xia, Chengwan; Pu, Yumei; Zhang, Qian; Hu, Qingang; Wang, Yuxin (Frontiers in Endocrinology, 2023)
Background: With the frequently use of Bisphosphonates (BPs), the morbidity of bisphosphonate-related osteonecrosis of the jaw (BRONJ) was also increasing. However, its prevention and treatment remains faced with huge challenge. This study aimed to illuminate the influence of BPs administration in the rat mandible and explore the feasibility of discriminating BRONJ lesion bone with Raman spectroscopy. Materials and Methods: Firstly, we explored the time-dependent and mode-dependent effects of BPs administration on the rat mandible with Raman spectroscopy. Secondly, BRONJ rat model has been constructed and the components of lesion bone and healthy bone has been analyzed with Raman spectroscopy. Results: When only BPs was administrated, no rats showed BRONJ symptoms and no difference could be found in Raman spectral. But when combined with local surgery, six (6/8) rats showed BRONJ symptoms. The Raman spectral also showed significance difference between lesion bone and healthy bone. Conclusion: In the progression of BRONJ, both BPs and local stimulation play an important role. Both BPs administration and local stimulation need to be controlled in preventing BRONJ. Moreover, BRONJ lesion bone in rat could be discriminated with Raman spectroscopy. This novel method would become a complement in the treatment of BRONJ in the future.